Morphological and Functional Retinal Assessment in Epiretinal Membrane Surgery. (2nd November 2017) - Donati, Simone; Caprani, Simona Maria; Semeraro, Francesco; Vinciguerra, Riccardo; Virgili, Gianni; Testa, Francesco; Simonelli, Francesca; Azzolini, Claudio
ABSTRACT: Purpose : To analyze functional and morphological findings after surgery for idiopathic epiretinal macular membrane (IEMM). Materials and Method s: Twenty eyes of 20 patients affected by IEMM underwent 23-Gauge surgery. Morphological and functional examinations were assessed at baseline and at 30, 90, and 180 days after surgery. SD-OCT evaluated foveal morphology and thickness, photoreceptor inner/outer segment junction, and external limiting membrane. Functional assessment evaluated visual acuity, retinal sensitivity, and fixation patterns. Statistical analysis was performed with the Student's t test and Pearson correlation test. Results : Mean central retinal thickness (CRT), visual acuity (VA), and retinal sensitivity (RS) at baseline were respectively 494.90 ± 38.73 µm, 0.55 ± 0.08 LogMAR, and 11.13±1.02; after surgery, at day 180, we observed a significant decrease in mean CRT to 326.90±32.68 µm, an increase in mean VA to 0.33 ± 0.05 LogMAR (p < 0.05), and in mean RS to 13.25 ± 0.73 dB (p < 0.05). A stable fixation increased from 40% of patients at baseline to 75% of patients at day 180 (p < 0.05). Discussion : IEMM surgery results in continuous improvement in visual function, not only at month one but also beyond month six, due to the progressive reduction of residual intraretinal edema and recomposition of retinal layers.